SPECTROPHOTOMETRIC ANALYSIS OF Pb, Cd, Cu, Fe AND ZnAMOUNTS IN MILK AND MILK PRODUCTS (Universal International Scientific Journal, 2026)
This article studies the content of heavy metal elements (Pb, Cd) and microelements (Cu, Zn, Fe) in milk and dairy products produced in the Jizzakh region [1-3]. The atomic absorption spectrophotometry method was used during the study. The results were evaluated from the point of view of food safety. The obtained data are important for regional environmental monitoring [4]
Keywords: milk; heavy metals; cadmium